Cartografía de la epigrafía paleohispánica I. Las téseras de hospitalidad (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
In this article are presented and explained three maps on the celtiberian tesserae of hospitality: 1.- Map of the distribution of findings; 2.- Map of the distribution of civic communities mentioned in the inscriptions; 3.- Map of the relationship between the communities documented in the tesserae.
Keywords: Cartography; Palaeohispanic Epigraphy; Tesserae of Hospitality; Celtiberian Language; City